Synthesis and biological evaluation of hydroxamate isosteres of acidic cannabinoids - Amin, Hawraz Ibrahim M.; Ruiz-Pino, Francisco; Collado, Juan A.; Appendino, Giovanni; Tena-Sempere, Manuel; Munoz, Eduardo; Caprioglio, Diego (Frontiers in Natural Products, 2023)
Despite their early discovery, the bioactivity of acidic cannabinoids was long overlooked. Issues of stability and a pharmacological focus on Δ9-THC and its biological profile combined to relegate the non-narcotic native form of phytocannabinoids to a sort of investigational limbo. Recent studies have disclosed an attractive bioactivity profile for specific acidic phytocannabinoids but concerns about their limited stability have remained substantially unaddressed. To solve this issue, we have developed the hydroxamate derivatives of Δ8-tetrahydrocannabinolic acid-A (Δ8-THCA-AH, 6) and cannabidiolic acid (CBDAH, 5) as novel acidic cannabinoid bioisosteres, and we report here their synthesis and bioactivity profile against specific cannabinoid targets, as well as promising in vivo activity in a murine model of polycystic ovary syndrome (PCOS) associated with obesity.